Seasonal variations of multi-biomarker responses to metals and pesticides pollution in M. galloprovincialis and T. decussatus from Homa Lagoon, Eastern Aegean Sea. (April 2019) - Uluturhan, Esin; Darılmaz, Enis; Kontas, Aynur; Bilgin, Mustafa; Alyuruk, Hakan; Altay, Oya; Sevgi, Selin
Abstract: Biomarkers (CAT, SOD, GPx, and AChE) were investigated in hepatopancreas and soft tissues of mussels ( Mytilus galloprovincialis ) and clams ( Tapes decussatus ) in response to metal and pesticide pollutions in Homa Lagoon. Mussel and clam samples were seasonally collected in January, May, August and November 2015. According to the results, higher metal concentrations determined in the soft tissues of both species in January. Hepatopancreas was found to accumulate higher levels of metals than soft tissue. Metal deposition potential in clams were higher than mussels. Pesticide levels were below detection limits in clams. In mussels, only 4, 4′-DDE was detected in soft tissues and hepatopancreas in November. Highest AChE, CAT, SOD and GPx activities in mussels were determined in January. On the other hand, maximum AChE and CAT activities in clams were found in November. Seasonal variations of metals and biomarker levels might be related to species-specific physiology and environmental conditions. Highlights: Seasonal variations of biomarker responses to metals and pesticides levels investigated in mussel and clam. Maximum AChE, CAT, SOD and GPx activities in mussels were found in January. Maximum AChE and CAT activities in clams were detected in November. Highest metal concentrations were generally observed in January. Only 4, 4′-DDE was found in mussels.